(untitled) (Perner’s Contacts, 2022)
3D printing of metal parts was investigated in this research work, which connecting to the supporting of model. The connection between the support and the model is important form the viewpoint of the mechanical fixturing, the heat conduction, the removability of the support and the success of printing. In this research work, some support and tooth parameters such as the top length, the hatch distance, and base length, tooth height were investigated to create a model-support connection strength map. This knowledge makes it possible to select the most appropriate connection type between the support and the model by the requirements specified in different cases. The strength of the support-model connection was characterized by the shearing properties using the torsion test. The results are illustrated and compared by different support parameters and materials. The 316L stainless steel and Ti6Al4V alloy were investigated.